Can reproductive traits help to explain the coexistence of mud crabs Panopeus (Decapoda: Panopeidae)? A case of two sympatric species inhabiting an impacted mangrove area of Southern Brazil. Issue 3 (3rd July 2018) - Peres, Pedro A.; Terossi, Mariana; Iguchi, Jully; Mantelatto, Fernando L.
Abstract: Coexistence among species is commonly related to niche divergence. However, congenerics usually are very similar in their microhabitat selection and food consumption. Thus, divergent life history strategies may represent the mechanism that allows sympatry in related species. Here, we describe and compare reproductive features in two sympatric mud crabs Panopeus americanus and P. occidentalis in an impacted mangrove area in Southern Brazil. As these species are ecologically similar, we hypothesize that these species diverge in their reproductive traits, which could explain their coexistence. Crabs were collected every two months from September 2004 to July 2006. Reproductive features such as number and size of ovigerous females, breeding season, fecundity, reproductive output, and embryo volume were assessed. Panopeus americanus produced embryos during the entire sampled period, while P. occidentalis produced only between September and March. Panopeus americanus produced more embryos considering the size of the species, had significantly lower embryo volume, and higher reproductive output than P. occidentalis . These data permit to classify P. americanus as an r-strategist and P. occidentalis as a K-strategist regarding their reproductive traits. In conclusion, our results support the hypothesis that divergent reproductive features may allow coexistence of these mud crabs.